2015
DOI: 10.1371/journal.pone.0113047
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Fluid Adenosine Deaminase (Pfada) in the Diagnosis of Tuberculous Effusions in a Low Incidence Population

Abstract: IntroductionPrevious studies have assessed the diagnostic ability of pleural fluid adenosine deaminase (pfADA) in detecting tuberculous pleural effusions, with good specificity and sensitivity reported. However, in North Western Europe pfADA is not routinely used in the investigation of a patient with an undiagnosed pleural effusion, mainly due to a lack of evidence as to its utility in populations with low mycobacterium tuberculosis (mTB) incidence.MethodsPatients presenting with an undiagnosed pleural effusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
(27 reference statements)
0
12
1
1
Order By: Relevance
“…Specificity of ADA in low prevalence areas has also been estimated. In a study done in north-western Europe, 338 patients with effusions were analyzed, and when an ADA cut-off of 35 U/L was used in combination with lymphocytic effusions, sensitivity was 90.9% and specificity was 98.9% [6]. In our study, pleural fluid CBNAAT was found to be positive in only 32% of cases, and rifampicin resistance was seen in 8.3%.…”
Section: Discussionmentioning
confidence: 48%
“…Specificity of ADA in low prevalence areas has also been estimated. In a study done in north-western Europe, 338 patients with effusions were analyzed, and when an ADA cut-off of 35 U/L was used in combination with lymphocytic effusions, sensitivity was 90.9% and specificity was 98.9% [6]. In our study, pleural fluid CBNAAT was found to be positive in only 32% of cases, and rifampicin resistance was seen in 8.3%.…”
Section: Discussionmentioning
confidence: 48%
“…Indeed, the paucibacillary aspect of tuberculous pleural effusion renders diagnosis difficult. Even in low incidence populations, pleural fluid measurement of ADA showed a high negative predictive value of 99.7% and a good sensitivity of 85.7% . Specifically, ADA2 is elevated in tuberculous pleural effusion and a reduction in ADA2 correlates with treatment response .…”
Section: The Human Adenosine Deaminase Enzymes: a Historical Perspectivementioning
confidence: 97%
“…Even in low incidence populations, pleural fluid measurement of ADA showed a high negative predictive value of 99.7% and a good sensitivity of 85.7%. 30 Specifically, ADA2 is elevated in tuberculous pleural effusion and a reduction in ADA2 correlates with treatment response. 27 ADA2 is produced by live MTB-infected macrophages.…”
Section: The Discovery Of Ada2 and The Genes That Encode It In Invementioning
confidence: 99%
“…They also demonstrated the levels were higher with advanced stage of disease and there remains a significant relationship between Fibulin 3 and survival (Pass et al, 2012). Further studies on Fibulin-3 have not been able to replicate these results, more recently Creaney et al demonstrated Fibulin 3 to be of low specificity for mesothelioma where a large number of patients with benign aetiology showing elevated levels of Fibulin 3 (Creaney et al, 2014).…”
Section: Fibulinmentioning
confidence: 99%